Analisis Model Persaingan antara Moda Kereta Api Eksekutif dengan Pesawat Udara Rute Yogyakarta â Jakarta. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The rapid increase of air transport especially for Yogyakarta-Jakarta route could influence of the decrease of train passengers. In the first four months in 2003, the data showed that it has decrease the number of executive train passengers until 40%. This is because the executive train has longer travel time. To be surviving, both of public transport operators have to understand some factors which give the influence of passenger behaviour for transport mode choice. . The aim of this study is to create a mode choice competition model between the executive train and the airplane for Yogyakarta â Jakarta route by using the stated preferences technique, in this technique respondents state their choice based on the existing conditions and the desire conditions. The mode choice has been modelled by discrete choice theory using binomial logit model, and the data analysis conducted by using LIMDEP verse 7.0. The results of the study indicated, the probability value for each mode was 22.78% for executive train, while it was 77.22% for airplane. The result of the goodness of fit test of model showed that the value for each indicator were 0,43 for rho-squared (p2), indicating that 43% of fare, travel time and access cost effected the mode choice, 99,12641 for chi-squared (i), 0,0159 for prediction success index (oi) and 76% for valid model. Moreover, the model application results with some scenarios of fare change and travel time showed that the fare change attribute of executive train was more sensitives than airplane mode, and all closely attributes in each mode were inelastic. It has been caused service characteristics of two modes were different significantly, particularly travel time.